TESTING OF WELDED REINFORCING BARS FOR ELONGATION AND PROCESS SIMULATION - Sherov, Karibek; Yessirkepova, Aiym; Abisheva, Nazerke; Serova, Rauza; Mussayev, Medgat; Tussupova, Sayagul; Zhakaba, Aizhan; Ashurova, Nasiba (Journal of Applied Engineering Science, 2022)
The authors carry out research on the development of technology for the manufacture of concrete products using non-dimensional waste of reinforcing bars, plain bars and wire rods. The studies carried out in the conditions of construction enterprises of the Republic of Kazakhstan, in particular the Karaganda region, have shown that this technology is advisable to use in the manufacture of concrete products such as bar lintels. As a result of the research carried out, a construction of a bar lintel was established, which is made of a concrete mixture with the addition of man-triggered waste and a space frame, reinforcing bars of which are welded from non-dimensional segments of reinforcement. This article presents the results of testing samples of reinforcing bars connected by friction welding and modeling the static tensile testing process with the determination of the tensile strength depending on the loads. At various loads, the stress on the surface of the reinforcing bar is less than 600 MPa, which corresponds to regulatory documents. At the same time, the maximum stresses are formed in the base metal, yet there is the least tension in welded seam. The test results showed the possibility of using welded reinforcing bars from non-dimensional segments of reinforcement in the manufacture of concrete products, in particular bar lintels.